BIMBINGAN TEKNIS PENGOLAHAN PAKAN MELALUI MESIN CHOPPER PADA KELOMPOK PETERNAK LONGGIDA BERSATU, KELURAHAN WATULONDO, KECAMATAN PUUWATU, KOTA KENDARI - Musram Abadi; La Ode Nafiu; Takdir Saili; Firman Nasiu; Muh Haidir Hakim; Gerhana Gerhana; Muhammad Darnawansyah; Andi Baso Gunawan; Aldi Surad; La Ode Fardit (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2026)
One solution that can be implemented to address feed management issues is through the provision of and training in the application of feed processing technology using a chopper machine. This program aims to equip Balinese cattle farmers with the knowledge and skills to process local feed ingredients efficiently and sustainably through the application of appropriate technology. Technical guidance on feed processing using a chopper machine was conducted by a team of lecturers from the Faculty of Animal Science at Halu Oleo University in October 2025 at the Longgida Bersatu Farmers’ Group, Watulondo Village, Puuwatu Subdistrict, Kendari City. Participants in the PKMI-UHO program included key stakeholders, such as 5 experts from the Faculty of Animal Science at Halu Oleo University (UHO) in Kendari, 15 farmers from the Longgida Bersatu Partner Group, 5 representatives from the Agricultural Extension Center (BPP), and several representatives from the Watulondo Village government. The implementation method utilized a participatory and practical approach, including an educational session on the importance of high-quality feed and hands-on field training covering equipment familiarization, machine chopper operation, feed material chopping, simple formulation, and feed storage techniques. The results of the activity show that the use of a chopper machine can save time, labor, and production costs. Farmers gained new knowledge and technical skills in feed processing, as well as an awareness of the importance of applying appropriate technology to improve business efficiency. Furthermore, this initiative strengthened cooperation and the self-reliance of livestock groups in managing their operations professionally. Consequently, the development of Bali cattle based on forage feed, facilitated by chopper machines, has taken place in Kendari City.